Pengalaman Komunikasi Pelajar Usia 17 Tahun pada Layanan KTPel Pemula di Kabupaten Solok - Muhamad Syamsul Bachri; Ernita Arif; Asrinaldi . (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Ownership of an Electronic Identity Card (Kartu Tanda Penduduk Elektronik or KTPel) is a legal obligation for Indonesian citizens upon reaching the age of 17, as mandated by national legislation. In this study, 17-year-old citizens are represented by senior high school students who serve as the research participants. Although various service facilities are available, high school student participation remains low due to communication problems. This study aims to examine the communication experiences of 17-year-old students in accessing beginner KTPel enrollment services in Solok Regency. The research employed a qualitative method using the Interpretative Phenomenological Analysis (IPA) approach. Data were collected through semi-structured interviews with five students aged 17 years who had participated in beginner KTPel enrollment services. The data were analyzed using the IPA method with the assistance of NVivo software. The research results reveal students' communication experiences through four main themes.: (1) social communication shapes students’ awareness and perceptions of KTPel; (2) the characteristics of service communication influence students’ comfort and trust in public services; (3) psychological and situational barriers generate hesitation among students in accessing KTPel services; and (4) KTPel is interpreted as a symbol of legal identity, adulthood, and social recognition.